Answer:
a) A-B = { 1 , 3, 5 }
b) The remainder is 50
c) f + g)(x) = x⁴+ 5x³
d) ![\frac{dy}{dx} = \frac{2x- y^3(3x^2)) }{ 1- x^3 3y^2}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B2x-%20y%5E3%283x%5E2%29%29%20%20%20%20%20%7D%7B%201-%20x%5E3%203y%5E2%7D)
Step-by-step explanation:
Step(I):-
1) a)
Let A = { 1, 3, 5, 7 } and B = { 7 , 14 , 21 }
A - B = {1,3,5,7} - { 7,14,21}
A - B = { 1 , 3, 5}
b)
Given f (x)=3x³−11x−48
x-1 ) 3 x³ - 11x -48 (- 3x²-3x -2
-3<u>x³ +3x</u>²
3x²-11x-48
<u> -3x²+9x</u>
<u> </u> 2x -48
-2x +2
<u> </u>
50
The remainder is 50
c) Given f(x) = x³ and g(x) = x + 5
(f. g)(x) = f(x) .g(x) = x³ . (x+5) = x³(x) + 5 x³ = x⁴+ 5x³
d)
Given function y = 3 + x²+x³y³ ...(I)
By using derivative formulas
y = xⁿ
![\frac{dy}{dx} = n x^{n-1}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20n%20x%5E%7Bn-1%7D)
Apply d/dx ( UV) = U V¹ + V U¹
Differentiating equation (I) with respective to 'x' , we get
![\frac{dy}{dx} = 0 + 2x + ( x^3 3y^2(\frac{dy}{dx} )+ y^3(3x^2))](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%200%20%2B%202x%20%2B%20%28%20x%5E3%203y%5E2%28%5Cfrac%7Bdy%7D%7Bdx%7D%20%29%2B%20y%5E3%283x%5E2%29%29)
![\frac{dy}{dx} = \frac{2x- y^3(3x^2)) }{ 1- x^3 3y^2}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B2x-%20y%5E3%283x%5E2%29%29%20%20%20%20%20%7D%7B%201-%20x%5E3%203y%5E2%7D)